2017
DOI: 10.3390/nu9070752
|View full text |Cite|
|
Sign up to set email alerts
|

Fruit and Juice Epigenetic Signatures Are Associated with Independent Immunoregulatory Pathways

Abstract: Epidemiological evidence strongly suggests that fruit consumption promotes many health benefits. Despite the general consensus that fruit and juice are nutritionally similar, epidemiological results for juice consumption are conflicting. Our objective was to use DNA methylation marks to characterize fruit and juice epigenetic signatures within PBMCs and identify shared and independent signatures associated with these groups. Genome-wide DNA methylation marks (Illumina Human Methylation 450k chip) for 2,148 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…For example, a recent study showed that fruit and juice epigenetic signatures as measured by DNA methylation marks are associated with independent immunoregulatory pathways, suggesting that the health benefits of fruit and juices are distinct. The identification of such differences between foods is the first step toward personalized nutrition [ 53 ].…”
Section: Nutritional Epigeneticsmentioning
confidence: 99%
“…For example, a recent study showed that fruit and juice epigenetic signatures as measured by DNA methylation marks are associated with independent immunoregulatory pathways, suggesting that the health benefits of fruit and juices are distinct. The identification of such differences between foods is the first step toward personalized nutrition [ 53 ].…”
Section: Nutritional Epigeneticsmentioning
confidence: 99%
“…Two longitudinal studies (521 subjects; 5 years) found that longer telomere length was significantly predictive of lower body weight, BMI, waist circumference, and dietary inflammatory index, and was associated with the higher fruit and fiber intake associated with high adherence to the Mediterranean diet [292,293]. The Framingham Heart Study Offspring cohort study observed that the intake of whole fruit up-regulated epigenetic gene function for immunosurveillance, and chromosome and telomere maintenance pathways, attributed to the effects of fruit fiber on colonic microbiota health [294]. Emerging fiber mechanisms associated with successful aging include: (1) enhancing the colonic probiotic microflora profile and production of SCFAs; (2) improving the colonic barrier function to protect against clinical inflammation; (3) increasing colonic peptides that are important in glucose and insulin homeostasis and lipid metabolism; and (4) mimicking many of the effects of caloric restriction including upregulation of genes involved in energy metabolism [295].…”
Section: Emerging Health Benefits Associated With Whole Fruits Andmentioning
confidence: 99%
“…The discovery of such differences among foods is the first step toward personalized nutrition. 264 Further, adequate nutrient levels are important for mitochondrial function as certain particular micronutrients play essential roles in energy metabolism and ATP production. 265 • Stem cell therapies strongly affect cellular senescence.…”
Section: Landscape View Of the Antiaging Strategies Research: Insight...mentioning
confidence: 99%